The first-person effect on environmental issues and religiosity - Ba Wazir, Ala Omar Mohammed; Mansoor, Hasan M.; Abdul Same’e, Somia (Open Access Publications Ltda., 2024)
Background : The First-Person Effect theory (FPE), also known as the reversed Third-Person Effect (TPE), posits that individuals are more likely to believe that media content directly influences them but has less impact on others, particularly when the media content is positive. Aim: this aims study to explore the effect of demographic characteristics and religiosity on the self-other perception discrepancy regarding environmental issues on SNS. Method: To explore the perceptual aspect of this theory, a quantitative approach was adopted to gauge how individuals perceive the influence of environment issues on Social Networking Sites (SNS), both on themselves and on others.The survey involved 357 student participants. Findings: The findings revealed that the participants perceive environmental issues on SNS as having a greater influence on themselves than on others, which supports the idea of FPE. However, the results indicated that religiosity did not correlate with the self-other perception discrepancy. Gender was found to have an impact on the self-other perceptual gap for environmental issues on SNS, whereas age and educational level did not .The study's implications suggest that it's essential not to judge others based on our own preferences and biases, and it highlights the tendency to prioritize our own interests over those of others.